Interactive Learning Media Based on Character Education in Indonesian Subjects for Grade 1 Elementary Schools - Samosir, Erni Damayanti Br; Agung, Anak Agung Gede; Suartama, I Kadek (Indonesian Values and Character Education Journal, 2023)
The impact of the development of technology and information certainly encourages educational institutions to continue to strive for programs that are by the abilities of students, technological advances, the environment and situations, conditions and needs of students. With the rapid development of information technology, it certainly has a major influence on the personality development of students, both positive and negative. For this reason, it is very important to re-arrange the pattern of personality education to balance and fortify the negative factors resulting from these developments. This study aims to develop interactive learning media products based on character education in the material of invitation sentences and response sentences in Indonesian subjects. This type of research is research and development of the ADDIE model design, which consists of five stages: Analyze, Design, Development, Implementation and Evaluation. The subjects of this study were 28 students of class I SD. Data collection methods and instruments used in this study were questionnaires and tests. This study found significant differences in Indonesian learning outcomes before and after using interactive learning media based on character education in Indonesian class I SD subjects. This study concluded that character education-based interactive learning media has proven effective in significantly increasing Indonesian learning outcomes.